2022
DOI: 10.1136/bjsports-2021-104795
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with acute respiratory illnesses in athletes: a systematic review by a subgroup of the IOC consensus on ‘acute respiratory illness in the athlete’

Abstract: ObjectiveTo review risk factors associated with acute respiratory illness (ARill) in athletes, including non-infectious ARill and suspected or confirmed acute respiratory infections (ARinf).DesignSystematic review.Data sourcesElectronic databases: PubMed-Medline, EbscoHost and Web of Science.Eligibility criteriaOriginal research articles published between January 1990 and July 2020 in English were searched for prospective and retrospective full text studies that reported quantitative data on risk factors assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 96 publications
(108 reference statements)
0
10
0
Order By: Relevance
“…In one of these studies, there was a Streptococcal outbreak in 23 athletes over 15 days (IR of 40.6/1000 athlete days) 63. In another study, seven clusters of different respiratory viral infections were recorded, with a ‘common cold’ in 44 athletes over 21 days, resulting in an IR of 26.7/1000 athlete days,64 which could have been caused by different risk factors such as the competition, international air travel and time difference 65. A large outbreak of infections from one pathogen in a small number of athletes is unusual and contrasts to the other study in this group 66…”
Section: Discussionmentioning
confidence: 94%
“…In one of these studies, there was a Streptococcal outbreak in 23 athletes over 15 days (IR of 40.6/1000 athlete days) 63. In another study, seven clusters of different respiratory viral infections were recorded, with a ‘common cold’ in 44 athletes over 21 days, resulting in an IR of 26.7/1000 athlete days,64 which could have been caused by different risk factors such as the competition, international air travel and time difference 65. A large outbreak of infections from one pathogen in a small number of athletes is unusual and contrasts to the other study in this group 66…”
Section: Discussionmentioning
confidence: 94%
“…A comprehensive review of the risk factors and biomarkers for both suspected and confirmed ARinf (n=24 studies) has been published by an IOC consensus subgroup 63. This review included 48 studies (19 390 athletes) and the majority (71%) of studies were self-reported ARill in athletes.…”
Section: Risk Factors Associated With Arinf In Athletesmentioning
confidence: 99%
“…A comprehensive review of the risk factors and biomarkers for both suspected and confirmed ARinf (n=24 studies) has been published by an IOC consensus subgroup. (63) • Vitamin D deficiency cannot be diagnosed by typical symptoms and clinical signs (clinical syndrome) alone, and laboratory tests are required for formal identification.…”
Section: Risk Factors Associated With Acute Respiratory Infections In...mentioning
confidence: 99%
“…In a real-life situation, HA may be combined with additional stressors such as travel, poor nutrition, and sleep deprivation, which could elevate the neuroendocrine response and thereby increase the risk for immunosuppression [ 2 ]. On the other hand, HA is mainly performed by elite athletes and highly trained military personnel, who may be less vulnerable to exercise-induced immunosuppression than our recreationally active participants [ 10 , 22 , 49 ]. Based on our findings, HA can be used to successfully induce heat adaptations in the weeks leading up to athletic competition or military deployment, without negatively affecting s-IgA availability, URTS risk and wellness.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Salivary immunoglobulin-A (s-IgA) has been studied extensively and research suggests that s-IgA availability diminishes with intensified training periods, resulting in elevated URTS risk [ 12 , 13 ]. Indeed, a recent systematic review identified both increased training intensity and reduced s-IgA as risk factors for the development of clinically diagnosed upper respiratory tract infection [ 10 ]. It should be noted, however, that URTS do not necessarily have an infective origin, but can also result from factors such as allergies or asthma [ 14 ], clouding the relationship between s-IgA and URTS.…”
Section: Introductionmentioning
confidence: 99%